Queue System Using Single Channel Single Phase For Gas Station Customers With An Arena Simulation Approach - Arsal, Muhammad; Maulana, Ihsan; Firdaus, Afdal Asyuri (International Journal of Global Operations Research, 2025)
The efficiency of the queuing system at a Public Fuel Filling Station (SPBU) is one of the crucial factors in maintaining smooth operations and increasing customer satisfaction. This study specifically analyzes the performance of the queuing system with a single channel single phase model at a gas station using a simulation approach assisted by Arena Simulation Software. The main focus of this study is to evaluate a number of performance indicators, such as average customer waiting time, queue length, server utilization rate, and service capacity that can be achieved under existing conditions and after the improvement scenario is implemented. Primary data was collected through direct observation in the field during peak hours, which were then processed and analyzed using probability distributions to model customer arrivals and service times. The simulation results show that the existing system has a very high server utilization rate, approaching 100%, indicating a potential risk of overload, although the average customer waiting time is relatively minimal. However, this performance can only be maintained under certain conditions and is at risk of decreasing significantly if there is a surge in customers beyond predictions. Simulation of the improvement scenario by significantly increasing the number of servers and operators succeeded in reducing the server utilization rate to the optimal level, shortening service time, and increasing the service capacity of the gas station. This proves that managerial intervention through the addition of service resources is a strategic step to increase operational efficiency.